Implementasi Internet of Things Pada Alat Penimbangan Muatan Truk Berbasis RFID - Alpha Rabbi Sugara; Ahmad Taqwa; Abdul Rakhman (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
In the world of transportation, weigh bridges have important funding for freight transport fleets, one of which is trucks. The higher the distribution of goods that occur, the more trucks that exceed the maximum load circulate on the highway.. Control of truck load control at weigh bridges is still not optimal because it is still recording cargo manually. As a result, traffic jams and illegal collections often occur around weigh stations. From the above problems, a tool that can automatically load RFID-based trucks using a load cell sensor is made, the process of paying truck loads that exceeds the maximum load using E-Money and the weighing data of trucks will be sent directly to government stakeholders using the Internet method of Things (IoT) in order to make it easier for officers at weigh stations to do work. This weighing device uses a Raspberry pi microcontroller as a sensor controller and RFID as a truck detector.